1996
DOI: 10.1105/tpc.8.4.687
|View full text |Cite
|
Sign up to set email alerts
|

Duplications That Suppress and Deletions That Restore Expression from a Chalcone Synthase Multigene Family.

Abstract: Seed coat color in soybean is determined by four alleles of the classically defined I (inhibitor) locus that controls the presence or absence as well as the spatial distribution of anthocyanin pigments in the seed coat. By analyzing spontaneous mutations of the I locus, we demonstrated that the I locus is a region of chalcone synthase (CHS) gene dupllcations. Paradoxically, deletions of CHS gene sequences allow higher levels of CHS mRNAs and restore pigmentation to the seed coat. The unusual nature of the I lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
201
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(207 citation statements)
references
References 15 publications
5
201
0
1
Order By: Relevance
“…3d and Supplementary Fig. 11b), respectively 21 .We also detected a GWAS signal responsible for purple or white flower color at the W1 locus 22 and a GWAS signal corresponding to seed coat color variation at the I locus [23][24][25] . We found that these two signals underwent selection during domestication and improvement, respectively (Supplementary Fig.…”
Section: Supplementary Tables 8 and 9)mentioning
confidence: 54%
“…3d and Supplementary Fig. 11b), respectively 21 .We also detected a GWAS signal responsible for purple or white flower color at the W1 locus 22 and a GWAS signal corresponding to seed coat color variation at the I locus [23][24][25] . We found that these two signals underwent selection during domestication and improvement, respectively (Supplementary Fig.…”
Section: Supplementary Tables 8 and 9)mentioning
confidence: 54%
“…The inhibition of seed coat pigment synthesis, or the dominance of the absence of pigment over its presence, has been demonstrated in a recent study in soybean (Todd and Vodkin 1996). In that study, the absence of the pigment in the seed coat was controlled by a dominant allele, l, which inhibited pigment synthesis whereas the recessive allele, i, conferred a pigmented seed coat phenotype.…”
Section: Discussionmentioning
confidence: 95%
“…In genotypes homozygous for the l allele (yellow seeds) and l i (yellow seeds with pigmented hilum), the chalcone synthase enzyme activity was seven to ten fold lower as compared with genotypes homozygous for i alleles (pigmented seed coat). Todd and Vodkin (1996) also indicated that chalcone synthase was coded by a family of seven duplicated genes, and their partial deletion restored pigment synthesis. This observation of soybean seed colour inheritance is the first publication that provides molecular evidence for the existence of a repressor locus that controls seed coat pigment synthesis, and we believe that our segregation data in B. carinata could be interpreted on the same basis, even though we have no molecular evidence for the presence of a repressor locus.…”
Section: Discussionmentioning
confidence: 99%
“…Structural gene rearrangements may also have unpredictable consequences on gene expression. The I locus controlling soybean seed coat coloration comprises several chalcone synthase genes that interact to produce a variety of pigmentation phenotypes (Todd and Vodkin, 1996). Allelic variation at the Ep locus of soybean is naturally occurring and commercially important since this affects the amount of peroxidase enzyme contained in the seed coat.…”
Section: Discussionmentioning
confidence: 99%